Competition Policy and Innovation - Peter Møllgaard; Jo Lorentzen (Copenhagen Business School (CBS), Department of Economics, 2006)
We briefly review the rationale behind technological alliances and provide a snapshot of their role in global competition, especially insofar as it is based around intellectual capital. They nicely illustrate the increased importance of horizontal agreements and thus establish the relevance of the topic. We move on to discuss the organisation of industries in a dynamic context and draw out consequences for competition policy. We conclude with an outlook on the underlying tensions between technology alliances, competition policy, and industrial policy.
hdl:10398/7635
Keywords: L40; L50; O31; 330; Competition policy; innovation; alliances; industrial policy